Comparative Hypoglycemic Property of Aqueous and Ethanolic Extracts of Viscum album (Mistletoe) and Their Effects on Body and Organ Weights of Diabetic Rats (Rattus norvegicus). - P.C, Chikezie; K.M.E, Iheanacho (Pharmacognosy Communications)
Plants are veritable sources of bioactive principles with profound therapeutic and medicinal value. The present study sought to determine, on comparative basis, the capacities of aqueous and ethanolic leaf extracts of Viscum album to ameliorate hyperglycemia and their effects on the body and visceral organ weights of experimental animals. Preparation of aqueous and ethanol/water (ratio 2:1; v/v) extracts of V. album was according to standard methods. Hyperglycemia was induced in 12 h fasted animals by intra-peritoneal injection of 0.1 mol/L alloxan monohydrate in phosphate buffer saline (PBS) solution (pH =7.4) at a dose of 140 mg/kg per body weight (b/w). Blood samples were drawn from the rats at regular intervals of 2 days for 14 days and measured for fasting blood glucose (FBG) using spectrophotometric methods. The body weight (b/w), pancreas, liver, kidney, heart and spleen of the rats were measured with electronic weighing balance. Comparative analyses showed that the aqueous leaf extract of V. album exhibited greater capacity to lower % FBG levels than the corresponding ethanolic leaf extract within the experimental time intervals of 0 day ≤ t ≤ 6 days; p > 0.05. In contrast, at t > 6 days, ethanolic leaf extract of V. album showed greater capacity to lower % FBG levels than corresponding the aqueous leaf extract; p < 0.05. Hyperglycemic rats without glycemic control exhibited 6.55 ± 1.08 % loss in b/w. Increases in kidney and heart weights of the test groups were not significantly different (p > 0.05) from the control (group C-N). Untreated diabetic rats showed significant (p < 0.05) increases in pancreas, liver and spleen weights compared to the group C-N. The therapeutic thresholds of the leaf extracts might be in connection with pharmacognostic dynamics coupled with toxicological outcomes of the administered leaf extracts.
Keywords: Fasting blood glucose; Rattus norvegicus; visceral organ; Viscum album; diabetes mellitus; mistletoe